Analisis Break Even Point (BEP) Sebagai Perencanaan Laba Pada UMKM Kerupuk Asoy Rengasdengklok Karawang - Yessy Shafira Danti Widyasari; Sihabudin Sihabudin; Robby Fauji (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
UMKM Kerupuk Asoy is a business that produces crackers made from wheat flour and starch. The average production carried out by UMKM Asoy Crackers in a month reaches 420 to 480 bales. Break even point (BEP) analysis is an analytical technique used to determine conditions where a company in carrying out its activities does not make a profit and does not suffer a loss or the amount of income is equal to the amount of costs incurred. The aim of this research is to find out how much break even point and margin of safety experienced and achieved UMKM Kerupuk Asoy in August 2023 and to make a profit plan in October 2023 to achieve the profits expected UMKM Kerupuk Asoy. This research uses break even point data analysis and margin of safety analysis. The method used in this research is a quantitative descriptive approach by presenting a summary of the data and values calculated based on the data collected. The results of this research show that there is a difference in achieving the break-even point in rupiah and quantity, this is due to differences in sales volume. Keywords: UMKM, Break Even Point, Margin of Safety, Profit Planning